2016
DOI: 10.1016/j.ygyno.2016.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, treatment and outcomes of women with immature ovarian teratoma, 1998–2012

Abstract: Objective To explore the presentation, management and outcomes of adult women diagnosed with immature ovarian teratoma. Methods The National Cancer Database (NCDB) was used to identify women ≥18 years of age diagnosed with an immature teratoma from 1998–2012. We analyzed demographic, clinical and tumor characteristics, and treatment trends. Multivariable models were employed to examine predictors of adjuvant chemotherapy use and survival. Results We identified a total of 1045 adult women with immature tera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 21 publications
(30 reference statements)
2
12
0
3
Order By: Relevance
“…Ovarian teratomas contain tissue elements from at least 2 of the 3 germ cell layers and frequently display a disorganized mixture of mature tissues including skin and hair (ectoderm), neural tissue (ectoderm), fat (mesoderm), muscle (mesoderm), cartilage (mesoderm), bone (mesoderm), respiratory epithelium (endoderm), and gastrointestinal epithelium (endoderm). Teratomas can occur in the mature form, composed exclusively of mature tissues, or the immature form, which contains variable amounts of immature elements (usually primitive neuroectodermal tissue consisting of primitive neural tubules) in a background of mature teratoma [5]. Not infrequently, malignant GCTs of the ovary contain a mixture of different histologic subtypes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian teratomas contain tissue elements from at least 2 of the 3 germ cell layers and frequently display a disorganized mixture of mature tissues including skin and hair (ectoderm), neural tissue (ectoderm), fat (mesoderm), muscle (mesoderm), cartilage (mesoderm), bone (mesoderm), respiratory epithelium (endoderm), and gastrointestinal epithelium (endoderm). Teratomas can occur in the mature form, composed exclusively of mature tissues, or the immature form, which contains variable amounts of immature elements (usually primitive neuroectodermal tissue consisting of primitive neural tubules) in a background of mature teratoma [5]. Not infrequently, malignant GCTs of the ovary contain a mixture of different histologic subtypes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the patients received fertility-sparing treatment followed by adjuvant chemotherapy in 78% ( 13 ). Jorge et al ( 14 ), in a recent multivariate analysis, showed that 90% of patients with immature teratoma were aged 18 to 39 years, three quarters of whom were early staged and could be treated conservatively combining fertility-sparing surgery and chemotherapy. Older age, advanced stage, and high grade are negative prognostic factors ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…2,6,7 IOTs are graded 1-3 depending 1 on the amount of atypia of the immature tissue. 2,8 There is a paucity of literature to date regarding the ultrasound features of immature ovarian teratomas, so the aim of this study was to characterise IOTs using grey-scale and Doppler ultrasonography and review the literature to help to refine the diagnosis and increase awareness of these tumours.…”
Section: Introductionmentioning
confidence: 99%